Mainlobe Jamming Suppression Using Improved Frequency Diverse Array with MIMO Radar. (2nd May 2019) - Li, Guang-ming; Zhang, Qun; Liu, Qi-yong; Liang, Jia; Wang, Dan; Zhu, Feng
Abstract : Frequency diverse array (FDA) has attracted much attention in recent years due to its range-angle-dependent beampattern. Multiple-input multiple-output (MIMO) radar can offer waveform diversity to increase the virtual aperture length for azimuth coherent focus processing in radar imaging. Combining the advantages of FDA and MIMO radar, FDA-MIMO radar can steer multiple beams to different targets in the same line of sight (LOS) of radar with different waveforms. In this paper, an improved FDA model with the logistic map is proposed to get the aperiodic and range-angle uncoupling beampattern. Based on the proposed FDA, combining the FDA-MIMO radar, the waveform and chirp rate jitter techniques are adopted to mainlobe jamming suppression. Simulation results show the effectiveness of the proposed method.